Effect of potassium iodide on luminescent and photovoltaic properties of organic solar cells P3HT-PCBM - Ibrayev, N.Kh.; Afanasyev, D.A.; Zhapabaev, K.A. (IOP Conf. Series: Materials Science and Engineering, 2016)
It has been investigated spectral-luminescence properties of polymer films, doped with potassium iodide (KI). Using of KI didn’t lead to the gradual changes of optical density of polymer films and the range of band gap semiconductor polymer P3HT. The fluorescence intensity of P3HT decreased and changed by use of KI. Using of 1% KI in polymer leaded to decrease of fluorescence lifetime. Influence of heavy atom on photovoltaic effect of organic solar cells has been investigated. 1% of KI in polymer film leaded to decrease of Isс and slightly decrease of Uос. Investigation shows that magnetic field does not affect on photovoltaic properties of cells P3HT-PCBM. Magnetic field increased of open circuit voltage and short circuit current of solar cells with 1% of KI. Study of electrical impedance of cells revealed the magnetic sensivity of solar cells with KI additives. The lifetime of free charge carriers increased in the magnetic field for solar cells with KI additives.
Keywords: Effect of potassium iodide; luminescent; photovoltaic properties; organic solar cells P3HT-PCBM